2015
DOI: 10.1186/s40360-015-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6*6, CYP2B6*18, Body weight and sex are predictors of efavirenz pharmacokinetics and treatment response: population pharmacokinetic modeling in an HIV/AIDS and TB cohort in Zimbabwe

Abstract: BackgroundEfavirenz (EFV) therapeutic response and toxicity are associated with high inter-individual variability attributed to variation in its pharmacokinetics. Plasma concentrations below 1 μg/ml may result in virologic failure and above 4 μg/ml, may result in central nervous system adverse effects. This study used population pharmacokinetics modeling to explore the influence of demographic and pharmacogenetic factors including efavirenz-rifampicin interaction on EFV pharmacokinetics, towards safer dosing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 42 publications
6
51
1
Order By: Relevance
“…BMI has been reported to be positively correlated with efavirenz V p /F, inversely correlated with AUC, and uncorrelated with terminal elimination half-life (3). However, other studies have also concluded there is no impact of weight or BMI on V p /F (27, 44) or did not report whether these effects were considered (15,25,40). Weight-normalized apparent volume of distribution has been reported to be 1.6-fold larger in females than males, suggesting that a sex-dependent factor influenced V/F independent of weight (16).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…BMI has been reported to be positively correlated with efavirenz V p /F, inversely correlated with AUC, and uncorrelated with terminal elimination half-life (3). However, other studies have also concluded there is no impact of weight or BMI on V p /F (27, 44) or did not report whether these effects were considered (15,25,40). Weight-normalized apparent volume of distribution has been reported to be 1.6-fold larger in females than males, suggesting that a sex-dependent factor influenced V/F independent of weight (16).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we retained the allometric FFM scalar and suggest that TBW-and FFM-scaled efavirenz clearance be further evaluated over a broader weight range that is biased toward obese subjects. Reported sex differences in efavirenz CL/F have been conflicting, with some studies showing associations (3,40) and others reporting no relationship (15,16). Similarly, differences in CYP2B6 expression and activity in human liver microsomes between sexes have been inconsistent in the literature (41-43).…”
Section: Discussionmentioning
confidence: 91%
“…With the EFV full-profile model developed, the sparse plasma concentrations were fit together with full-profile plasma data. As strong prior literature suggests that differences in CYP2B6*6 genotypes are linked to variability in exposure measures of EFV (22,34,(36)(37)(38), CYP2B6*6 genotype status was included as a modifier of clearance in the base model. Individuals with CYP2B6*1/*1, CYP2B6*1/*6, and CYP2B6*6/*6 genotypes were modeled with unique (thetas) for EFV clearance.…”
Section: Methodsmentioning
confidence: 99%
“…Being one of the potent drugs preventing mother to child transmission of HIV, EFV drug has been investigated for pharmacokinetic variability, therapeutic effects, and toxicity among different patient populations. [14][15][16] It has been observed that a very strict pharmacological concentration is a must in order to avoid virologic failure and tissue toxicity. Therefore, it was worth investigating the nanoformulation of EFV for anti-HIV activity and toxicity in GALT.…”
Section: Introductionmentioning
confidence: 99%